CANINE DERMATITIS IN THE DISTRICT OF MIRAFLORES, LIMA, PERU - Ceino, Franco (2018)
Canine dermatitis is one of the most common diagnoses in daily veterinary practice and aff ects a large number of thedog population. Th is research determined the type of dermatitis that occurred most often in daily consultations in threeVeterinary Clinics of Mirafl ores district, Lima, Peru. For this, we collected data from clinical histories from 2004 to 2014of dogs attended in this district. We analyzed and compared the sex, age and race of the animal along with the presence ofdermatitis. Out of 5968 medical histories, 1584 (26.54%) were positive for dermatitis. According to our data the highestnumber of cases reported in the classifi cation was dermatitis due to infectious agents with a total of 1144 cases (72.22%).Secondly, immunological dermatitis was found in 200 cases (12.62%) and, thirdly, there was allergic dermatitis seen in188 cases (11.86%). As for breeds, mixed-type canines had higher numbers of cases of dermatitis (20.45%) than purebreeds. Th e most aff ected age group corresponded to adult dogs, with 76.76% of cases.